The employment of optic coherence tomography in the diagnosis of papilledema - Yaney González Yglesias; Carlos E. Mendoza Santiesteban; Lillian G. León Veitía; Yosbelkys Martín Páez (Medisur)
Background: The optic coherence tomography constitute one of the most revolucionary tool in the ophtalmic diagnosis in the latest years, and is very useful in the papilledema studies. Objectives: Evaluate the optic coherence tomography useful in papilledema diagnosis. Methods: Prospective, observacional and analytic study made since may to october 2007 in the neuroophtalmology deparment, Ophtalmology Cuban Institute “ Ramón Pando ferrer”. Were studied 27 patients that presented a typical papilledema in the first episode at least with 2 months of duration. Results: The female sex was predominant with 27 of medium age. The medium thickness values of nervous fiber layer were stadistic important betwen the sectors (p=0.000). The nervous fiber layer thickness was predominant in order to frequency in lower, upper, nasal and temporal sectors. Conclusions: The optic coherence tomography constitute an useful instrument to papilledema diagnosis.